PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSET (ROA) PADA PT. GUDANG GARAM TBK PERIODE 2013-2023 - Nashrullah; Achmad Agus Yasin Fadli (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of the current ratio and debt-to-equity ratio on return on assets, both partially and simultaneously, at PT Gudang Garam Tbk for the period 2013-2022. The selected population consists of the financial statements of PT Gudang Garam Tbk, with the sample being the balance sheets and income statements for the period 2013-2022. This study uses a quantitative approach and a purposive sampling method. The analysis method includes calculating the results of each variable, conducting descriptive tests, classical assumption tests, simple and multiple linear regression, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. Based on the results of the study, using the t-test for partial effects, the current ratio has no significant effect on return on equity, with a significance value of 0.062 (greater than 0.05) and a t-value of 2.168 (less than the t-table value of 2.306). The debt-to-equity ratio showed no effect on return on equity, with a significance value of 0.000 (less than 0.05) and a t-value of 17.106 (less than the t-table value of 2.251). The results of the simultaneous testing for the effect of the current ratio and debt-to-equity ratio on return on equity indicated an effect, with a significance value of 0.629 and an F-value of 149.343 (greater than the F-table value of 4.46). The correlation coefficient test showed that the relationship is very strong, with a value in the range of 0.80-1.000. The determination coefficient test revealed an R square (R²) value of 0.974, indicating that the current ratio and debt-to-equity ratio together contributed 97.4% to return on equity, while the remaining 2.6% was influenced by other variables not examined in this study.